2015
DOI: 10.1177/0146645315577539
|View full text |Cite|
|
Sign up to set email alerts
|

ICRP Publication 130: Occupational Intakes of Radionuclides: Part 1

Abstract: This report is the first in a series of reports replacing Publications 30 and 68 to provide revised dose coefficients for occupational intakes of radionuclides by inhalation and ingestion. The revised dose coefficients have been calculated using the Human Alimentary Tract Model (Publication 100) and a revision of the Human Respiratory Tract Model (Publication 66) that takes account of more recent data. In addition, information is provided on absorption into blood following inhalation and ingestion of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 156 publications
0
81
0
Order By: Relevance
“…These results extend those of Cai et al who found a significant reduction in serum cesium in SCZ 15 . As described in the Introduction, there is evidence that cesium shares similarities with potassium and competes with potassium for both active and passive membrane transport 31 , although, after intake, cesium is Moreover, cesium may also have some neuroprotective properties by inhibiting GSK3β, preventing caspase-3 activation and neuronal apoptosis, and attenuating peroxide-induced cell death 36 . These authors, therefore, conclude that given its good blood-brain-barrier penetration 33 , cesium may have some use in the treatment of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results extend those of Cai et al who found a significant reduction in serum cesium in SCZ 15 . As described in the Introduction, there is evidence that cesium shares similarities with potassium and competes with potassium for both active and passive membrane transport 31 , although, after intake, cesium is Moreover, cesium may also have some neuroprotective properties by inhibiting GSK3β, preventing caspase-3 activation and neuronal apoptosis, and attenuating peroxide-induced cell death 36 . These authors, therefore, conclude that given its good blood-brain-barrier penetration 33 , cesium may have some use in the treatment of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…and exhibits a substantially longer whole-body retention time than potassium31 . Moreover, changes in the permeability of the brain-CSF barrier may occur in response to trace elements including cesium as observed in Alzheimer's disease 32 .…”
mentioning
confidence: 97%
“…where, 10 -3 is a constant representing 1 mSv as an annual committed effective dose, N is the number of individual monitoring performed in a year, is the dose coefficient for inhalation or ingestion of radionuclide j, and is the fraction of the intake, called bioassay functions in the ICRP OIR [1], of radionuclide j remaining in the body or in the excretion sample after an elapsed time period t0.…”
Section: Drl and MC Values For The Selected Radionuclidesmentioning
confidence: 99%
“…Recently, the International Commission on Radiological Protection (ICRP) has published OIR (occupational intakes of radionuclides) report series for internal dosimetry of occupational intakes [1][2][3]. In Korea, several nuclear facilities operating nuclear power plants and a research reactor have carried out routine individual monitoring for JRPR radiation workers who are likely to be internally contaminated by radioactive materials with a form of unsealed sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation